1987
DOI: 10.1346/ccmn.1987.0350103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicate Species on the Transformation of Ferrihydrite into Goethite and Hematite in Alkaline Media

Abstract: Abstract--The transformation of ferrihydrite to goethite and/or hematite in alkaline media is strongly retarded by the presence of silicate species. These species probably stabilize ferrihydrite by adsorbing on the particles of ferrihydrite and linking them into an immobile network.At concentrations low enough for the transformation to proceed, silicate species promote the formation of hematite and hinder the nucleation ofgoethite. The presence of silicate species modifies the morphology of both reaction produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(163 citation statements)
references
References 31 publications
12
149
2
Order By: Relevance
“…Also, the relative position of hydroxyl groups on the surface is presumably altered, possibly leading to different sorption properties as compared to pure goethite. The incorporation of Si did not cause any change of the unit-cell dimensions as also shown by Cornell et al (1987) and Quin et al (1988). This indicates that the close association of this element with goethite occurs by occlusion and not by isomorphous substitution.…”
Section: Characteristics Of the Goethitessupporting
confidence: 57%
See 3 more Smart Citations
“…Also, the relative position of hydroxyl groups on the surface is presumably altered, possibly leading to different sorption properties as compared to pure goethite. The incorporation of Si did not cause any change of the unit-cell dimensions as also shown by Cornell et al (1987) and Quin et al (1988). This indicates that the close association of this element with goethite occurs by occlusion and not by isomorphous substitution.…”
Section: Characteristics Of the Goethitessupporting
confidence: 57%
“…In the presence of Si relatively large crystals are formed (sample GSi: length ~600 nm, width ~ 200 nm) which are multi-domainic (Figure 2). This effect could be due to the presence of strongly sorbing silicate anions linking together goethite particles (Cornell et al 1987, Quin et al 1988. Furthermore, this sample exhibited the smallest X R D line-broadening of all samples.…”
Section: Characteristics Of the Goethitesmentioning
confidence: 89%
See 2 more Smart Citations
“…TEMs of samples taken during the earliest stages of the reaction showed that birnessite formed simultaneously with or even before hausmannite. Apparently, this birnessite formed by disproportionation from Mn(III) produced by oxidation of Mn(II) at the akaganrite surface: earlier studies (CorneU and Giovanoli, 1987) showed that addition ofMn 3 § solution (0.01 M) to KOH (0.01-1 M) led to rapid precipitation of birnessite. In the present work, more birnessite formed initially in the presence of high-surface-area, than lowsurface-area akaganrite, which is consistent with more extensive adsorption and, hence, oxidation of Mn(II) by the high-surface-area iron oxide.…”
Section: Reaction Products (Table 1)mentioning
confidence: 95%